2020
DOI: 10.1038/s41598-020-76744-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Streptococcus mutans and Candida albicans synergy by a commensal streptococcus

Abstract: Polymicrobial interactions in dental plaque play a significant role in dysbiosis and homeostasis in the oral cavity. In early childhood caries, Streptococcus mutans and Candida albicans are often co-isolated from carious lesions and associated with increased disease severity. Studies have demonstrated that metabolic and glucan-dependent synergism between C. albicans and S. mutans contribute to enhanced pathogenesis. However, it is unclear how oral commensals influence pathogen synergy. Streptococcus parasangui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Although several researchers have studied the impact of individual (or a few) members of the microbiome on C. albicans (as discussed in this review), the complexity of the microbiome poses challenges in gaining a more complete picture of how all the interactions within the microbiome. A recent example of the influence of a commensal bacterium on a PMB is found in the work of Huffines and Scoffield (2020) who found that the commensal bacterium, Streptococcus parasanguinis, influenced C. albicans-S. mutans PMB formation. In this context, S. parasanguinis decreased biofilm formation and restricted the incorporation of C. albicans into the PMB.…”
Section: Influence Of Environmental and Host Factorsmentioning
confidence: 99%
“…Although several researchers have studied the impact of individual (or a few) members of the microbiome on C. albicans (as discussed in this review), the complexity of the microbiome poses challenges in gaining a more complete picture of how all the interactions within the microbiome. A recent example of the influence of a commensal bacterium on a PMB is found in the work of Huffines and Scoffield (2020) who found that the commensal bacterium, Streptococcus parasanguinis, influenced C. albicans-S. mutans PMB formation. In this context, S. parasanguinis decreased biofilm formation and restricted the incorporation of C. albicans into the PMB.…”
Section: Influence Of Environmental and Host Factorsmentioning
confidence: 99%
“…Furthermore, the use of Lactobacillus plantarum CCFM8724 outperformed chlorhexidine in treating and preventing dental caries induced by C. albicans-S. mutans biofilm in vivo (Zhang et al, 2020). Similarly, antagonizing Streptococcus parasanguinis disrupted C. albicans-S. mutans biofilm by altering sugar metabolism and glucosyltransferase activity of S. mutans (Huffines and Scoffield, 2020), which is critical for EPS-matrix development and GtfB-mediated cross-kingdom interaction (Hwang et al, 2017;Kim et al, 2021). Another alternative approach for biofilm eradication is antimicrobial photodynamic therapy (aPDT).…”
Section: Alternative Antibiofilm Strategiesmentioning
confidence: 99%
“…mutans biofilm by altering sugar metabolism and glucosyltransferase activity of S . mutans (Huffines and Scoffield, 2020), which is critical for EPS‐matrix development and GtfB‐mediated cross‐kingdom interaction (Hwang et al ., 2017; Kim et al ., 2021). Another alternative approach for biofilm eradication is antimicrobial photodynamic therapy (aPDT).…”
Section: Therapeutic Approaches For Candida–bacterial Biofilm‐associa...mentioning
confidence: 99%
“…We previously demonstrated the ability of S. parasanguinis to inhibit the growth of S. mutans and caries development in a H 2 O 2 - and nitrite-dependent manner using a rat caries model ( Scoffield et al., 2019 ). Further, we have demonstrated that S. parasanguinis disrupts synergy between S. mutans and C. albicans in a contact and H 2 O 2 -independent manner ( Huffines and Scoffield, 2020 ). While bacterial and host-derived metabolites are known to shape oral polymicrobial communities and nitrite has been shown to aid oral commensal streptococci in the inhibition of diverse pathogens, no studies have observed how oral commensals such as S. parasanguinis influence the metabolomes of polymicrobial communities in the presence of nitrite.…”
Section: Introductionmentioning
confidence: 99%